2001
DOI: 10.1021/ac0011540
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Imaging ELISA Using an Imprinted Polymer as the Recognition Element Instead of an Antibody

Abstract: An imaging assay analogous to competitive enzyme immunoassays has been developed using a molecularly imprinted polymer instead of an antibody. The antigen 2,4-dichlorophenoxyacetic acid (2,4-D) was labeled with tobacco peroxidase, and the chemiluminescence reaction of luminol was used for detection. Microtiter plates (96 or 384 wells) were coated with polymer microspheres imprinted with 2,4-D, which were fixed in place by using poly(vinyl alcohol) as glue. In a competitive mode, the analyte-peroxidase conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 20 publications
0
77
0
2
Order By: Relevance
“…In this manner, near-monodispersed spherical beads can be prepared, and size and porosity can be fine-tuned thereby changing the polymerization conditions. This technique has been reported in MIP-based competition assays [71][72] and capillary electrochromatography [73][74], but only recently works have been published, in which it is clearly shown that precipitation polymerization can be a potentially fruitful technique for preparing chromatography-grade molecularly imprinted beads [75].…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…In this manner, near-monodispersed spherical beads can be prepared, and size and porosity can be fine-tuned thereby changing the polymerization conditions. This technique has been reported in MIP-based competition assays [71][72] and capillary electrochromatography [73][74], but only recently works have been published, in which it is clearly shown that precipitation polymerization can be a potentially fruitful technique for preparing chromatography-grade molecularly imprinted beads [75].…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…12 Glass beads were activated by boiling in NaOH for 10 min and washed with DI water and acetone. After drying, the beads were incubated overnight in a 2 % solution of APTMS in dry toluene and then washed with acetone and dried.…”
Section: Preparation Of Solid-phases For Different Templatesmentioning
confidence: 99%
“…One of the major drawbacks to work with MIPs in ELISA is the absence of a reproducible and straightforward method for coating microplate wells with the material. In the literature, there are several papers describing the applications of MIPs in ELISA, [8][9][10][11][12][13][14][15] but only a few demonstrate direct application of MIPs in the assays for quantitative detection of the target analytes. [8][9]16 In one example, the surface of the microplate wells was modified with a homopolymer of 3-aminophenylboronic acid, which was imprinted with ephedrine 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high costs and large size of these instruments are incompatible with the concept of -TAS. Chemiluminescence (CL) is a highly sensitive detection method widely used in flow-injection analysis [12], immunoassays [13] and conventional capillary electrophoresis [14,15]. Due to its simple optical devices, wide linear range, and the presence of many well-characterized systems, CL is uniquely suited to on-line detection for -TAS.…”
Section: Introductionmentioning
confidence: 99%